2010
DOI: 10.3347/kjp.2010.48.4.331
|View full text |Cite
|
Sign up to set email alerts
|

ExperimentalToxocara catiInfection in Gerbils and Rats

Abstract: Mongolian gerbils and Wistar rats were inoculated orally with 240 and 2,500 Toxocara cati embryonated eggs, respectively, to evaluate the larval recovery in different tissues and organs, such as the liver, lungs, heart, kidney, and skeletal muscles after 5, 30, 49, 70, and 92 days post-infection (PI). Larval recovery rates were 1.7-30.0% in Mongolian gerbils on days 5-92 PI and 0.2-3.8% in rats on the same days. These results indicate that Mongolian gerbils and Wistar rats are suitable experimental paratenic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Since most individuals do not manifest any pathognomonic symptoms, the actual prevalence rate of the infection remains to be elucidated, even in industrialized nations [34,35]. Considering that Toxocara parasites do not develop into adult stage in humans, coproscopy is unnecessary; thus, biopsy and direct parasite observation are the gold standard methods [36]. However, such examination is invasive and relies on the larval load and the infection phase [28].…”
Section: Discussionmentioning
confidence: 99%
“…Since most individuals do not manifest any pathognomonic symptoms, the actual prevalence rate of the infection remains to be elucidated, even in industrialized nations [34,35]. Considering that Toxocara parasites do not develop into adult stage in humans, coproscopy is unnecessary; thus, biopsy and direct parasite observation are the gold standard methods [36]. However, such examination is invasive and relies on the larval load and the infection phase [28].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely recognized source of human infection is ingestion of contaminated soil followed by paratenic hosts (2-7). The released larvae from the eggs or paratenic hosts enter the circulation which then invade and form granulomas in different tissues, including; liver, lungs, eyes, brain and other tissues (8,9). The prevalence of toxocariasis due to soil contamination with Toxocara spp.…”
Section: Introductionmentioning
confidence: 99%
“…Ten Mongolian gerbils (one-month-old males) and ten Wistar rats (one-month-old males) were assigned in ten experimental groups ( n = 2/group): each two animals of the same, were infected orally with approximately 240 and 2500 embryonated T. cati eggs, respectively [6, 13–15]. The eggs were derived from adult female worms and were embryonated according to our previous paper [16].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been reported that human can be infected by the ingestion of T. cati embryonated eggs with contaminated soil or eating larvae within paratenic hosts including birds and small rodents. There is little finding on the location of T. cati larvae in paratenic hosts including the eye as causative agents of human toxocariasis [5, 6]. …”
Section: Introductionmentioning
confidence: 99%